2017
DOI: 10.1093/hmg/ddx041
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex II regulates a distinct oxygen sensing mechanism in monocytes

Abstract: Mutations in mitochondrial complex II (succinate dehydrogenase; SDH) genes predispose to paraganglioma tumors that show constitutive activation of hypoxia responses. We recently showed that SDHB mRNAs in hypoxic monocytes gain a stop codon mutation by APOBEC3A-mediated C-to-U RNA editing. Here, we test the hypothesis that inhibition of complex II facilitates hypoxic gene expression in monocytes using an integrative experimental approach. By RNA sequencing, we show that specific inhibition of complex II by atpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Previously, we have shown that A3A-mediated RNA editing is induced by high cell density and hypoxia in hundreds of mRNAs in monocytes [15]. Furthermore, normoxic inhibition of the mitochondrial complex II by atpenin A5 (AtA5) and of the complex III by myxothiazol (MXT) mimics hypoxia and induces RNA editing as well as hypoxic gene expression in monocytes [39]. Since A3G-mediated RNA editing in NK and HuT78 cells is also induced by hypoxia, we tested the effect of these mitochondrial inhibitors on RNA editing in HuT78 cells cultured in normoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that A3A-mediated RNA editing is induced by high cell density and hypoxia in hundreds of mRNAs in monocytes [15]. Furthermore, normoxic inhibition of the mitochondrial complex II by atpenin A5 (AtA5) and of the complex III by myxothiazol (MXT) mimics hypoxia and induces RNA editing as well as hypoxic gene expression in monocytes [39]. Since A3G-mediated RNA editing in NK and HuT78 cells is also induced by hypoxia, we tested the effect of these mitochondrial inhibitors on RNA editing in HuT78 cells cultured in normoxia.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, SDHB protects against 3-nitropropionic acid-induced striatal degeneration. Interestingly, SDHB is suppressed in monocytes exposed to inflammation/hypoxia in an APOBEC3-mediated manner 50 . GO analyses identified altered hypoxic signalling in the HD although not in the patients with highest CAG size (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Atpenin A5 (atpenin) is an SDH inhibitor that binds in the ubiquinone binding pocket comprised of residues from SDH subunits B, C, and D, blocking the electron transfer between the enzyme and ubiquinone [44,45]. It is important to note that the inhibition of SDH with atpenin could not induce hypoxia mediated gene expression in monocytes [46] and a dose dependent reduction of cell survival after treatment with atpenin analogues has been shown [47].…”
Section: Introductionmentioning
confidence: 99%